Early Weaning: a Management Alternative for Florida Beef Cattle Producers - John Arthington (EDIS)
This document is AN131, one of a series of the Animal Sciences Department, Florida Cooperative Extension Service, Institute of Food and Agricultural Sciences, University of Florida. Original publication date March 2003.